Bilateral deep transcranial magnetic stimulation of motor and prefrontal cortices in Parkinson’s disease: a comprehensive review - Hanlon, Colleen A.; Lench, Daniel H.; Pell, Gaby; Roth, Yiftach; Zangen, Abraham; Tendler, Aron (Frontiers in Human Neuroscience, 2024)
Parkinson's Disease (PD) is a prevalent neurodegenerative disorder characterized by both motor and non-motor symptoms, many of which are resistant to currently available treatments. Since the discovery that noninvasive transcranial magnetic stimulation (TMS) can cause dopamine release in PD patients, there has been growing interest in the use of TMS to fill existing gaps in the treatment continuum for PD. This review evaluates the safety and efficacy of a unique multifocal, bilateral Deep TMS protocol, which has been evaluated as a tool to address motor and non-motor symptoms of PD. Six published clinical trials have delivered a two-stage TMS protocol with an H-Coil targeting both the prefrontal cortex (PFC) and motor cortex (M1) bilaterally (220 PD patients in total; 108 from two randomized, sham-controlled studies; 112 from open label or registry studies). In all studies TMS was delivered to M1 bilaterally (STAGE 1) and then to the PFC bilaterally (STAGE 2) with approximately 900 pulses per stage. For STAGE 1 (M1), two studies delivered 10Hz at 90% motor threshold (MT) while 4 studies delivered 1Hz at 110% MT. For STAGE 2 (PFC), all studies delivered 10Hz at 100% MT. The results suggest that this two-stage Deep TMS protocol is a safe, moderately effective treatment for motor symptoms of PD, and that severely impaired patients having the highest benefits. Deep TMS also improves mood symptoms and cognitive function in these patients. Further research is needed to establish optimal dosing and the long-term durability of treatment effects.